Gestión del talento humano en la hacienda Erikita De La Parroquia San Juan. - Gavilánez Piza, María Fernanda (2022)
For the present investigation, the theme Human Talent Management was chosen in the Erikita Hacienda of the San Juan Parish, this hacienda is located in the Los Ríos-San Juan Province, it is a company dedicated to the cultivation of Williams variety bananas, with the purpose of export. For the development of its activity the company has 350, Human Talent Management is a matter of vital importance since it is the perfect complement to any company. Therefore, the objective is to know the Management of Human Talent in the Hacienda Erikita, because the main problems are directly related to inefficient management regarding recruitment, selection, staff training and the factors that affect job performance. The methodology used was descriptive, which allowed collecting the necessary information for the investigation, on the other hand, the quantitative method was also used, since information collection techniques such as interviews and surveys were used. The results obtained were based on the data provided through the interview and the surveys that were applied correctly, allowing to know the inefficiencies that the Treasury currently presents due to the inadequate management of human talent, these same results allowed the conclusions drawn in this case of study.